The Use of Sour Soup (Annona murricata) Seed Powder as Acaricide on Cow and Goat - Yudha Fahrimal; Razali Daud; Adi Chandra; Syauki Iqbal; Roslizawaty Roslizawaty (Jurnal Kedokteran Hewan, 2010)
This research was aimed to study curative effect of sour soup seed powder on cattle invested with ticks and goat infected with scabies. This study was using 12 cattle invested with ticks and 12 goats with scabies. The cattle divided into 4 groups (S1, S2, S3 and S4) while goats were divided into 3 groups (K1, K2, and K3) equally. For cattle with ticks group S1 received water (control group), while group S2, S3, and S4 received 1%, 5%, and 10% sour soup powder respectively. Ticks that fell to the ground and not engorged were collected and identified. Statistical analysis showed that all concentrations of sour soup were effective in paralyzing and or killing ticks of the genera Boophilus sp. and Dermacentor sp. but were not effective against Rhipicepalus sp. For goats with scabies, groups K1, K2, and K3 received 1, 5 and 10% sour soup powder respectively mixed with water applied to whole area of infected and uninfected skin surrounding infected area. Number of mites per cm2 before and after treatment was counted. Statistical analysis showed that 1, 5, and 10% sour soup powder effective in reducing the number of scabies mites on day 1 and 7 after treatment and were significantly different from those number of mites before treatment (P0.01). Statistical analysis also showed that no significant difference among concentration of sour soup seed powder in decreasing the number of mites (P0.05).